Educating scholars : doctoral education in the humanities - Ehrenberg, Ronald G. (Princeton University Press, 2010)
Despite the worldwide prestige of America's doctoral programs in the humanities, all is not well in this area of higher education and hasn't been for some time. The content of graduate programs has undergone major changes, while high rates of student attrition, long times to degree, and financial burdens prevail. In response, the Andrew W. Mellon Foundation in 1991 launched the Graduate Education Initiative (GEI), the largest effort ever undertaken to improve doctoral programs in the humanities and related social sciences. The only book to focus exclusively on the current state of doctoral edu.